PENANGANAN BAHAN KIMIA BERBAHAYA PADA BAGIAN PENGECATAN MOBIL (STUDI KASUS: AUTO 2000 BODY AND PAINT BALIKPAPAN) - Azteria, Veza Azteria (Program Studi Kesehatan dan Keselamatan Kerja, 2019)
Chemicals hazardous are single or mixed chemical form based on chemical, physical characteristic and toxicology to the installation worker and environment (Regulation Minister of Labor RI No.187/MEN/1999). One of the industries used chemicals is automotive industries. Auto 2000 is one of the company for repairing and painting particular automotive vehicle body, the used various of chemicals and it can be caused a great impact to the health, especially if do not properly handle. The purpose of this research is to determine how far knowledge, attitude and practice can be used to handle the chemicals hazardous of car painting Auto 2000 Body and Paint Balikpapan. Combination of qualitative and quantitative studies is one of advantage if this research. Data obtained will be analyzed using effectiveness theory. The research subjects were used 30 employees in auto 2000 body and paint Balikpapan. Knowledge, attitude and handling of chemicals hazardous in the car painting auto 2000 body and pain Balikpapan is a satisfied category which the following category: knowledge ratio 85.2%, attitude ratio 89% and action 86.4%. Based on the characteristic of the respondent, age and formal education it finds out that significant effect handling of chemicals hazardous. But the most affect handling of chemicals hazardous are working period and followed by training frequency.